GEOLOGI DAN ANALISIS KUALITAS AIR SUMUR BERDASARKAN TOTAL DISSOLVED SOLID (TDS) DAN DERAJAT KEASAMAN (pH) DAERAH ALUVIAL MANGGAR, KOTA BALIKPAPAN - Jamaluddin Jamaluddin; Iwan Prabowo; A. Ibnu Taslim; Maria Maria (PETROGAS: Journal of Energy and Technology, 2022)
The need for clean water in the Manggar area is increasing yearly. However, the condition of cloudy, smelly, and colored water is a problem faced by people in this area. This study aimed to analyze the water quality of community wells based on the value of Total Dissolved Solids (TDS) and acidity (pH) in the alluvial plains of Manggar. Based on the research results, the value of Total Dissolved Solids (TDS) ranging from 27 ppm - to 338 ppm is classified as freshwater, while the Power of Hydrogen (pH) value ranging from 7.1 to 8.3 is alkaline. The results of the research on water quality in alluvial plains of Manggar based on these two parameters meet the requirements according to the threshold from the Ministry of Health of the Republic of Indonesia (Kemenkes RI). However, their smell and color are not suitable for consumption. The reason is that the rock units in the alluvial plains of Manggar area are still in the form of unconsolidated material, still in the form of loose clay-sized material, which can affect the quality of healthy water in the area.